Introduction: 'Address as Social Action Across Cultures and Contexts' from book: Address Practice as Social Action: European Perspectives - Norrby, Catrin (Palgrave Macmillan, 2015)
This is the introductory chapter of Address Practice as Social Action: European Perspectives. It is open access under a CC BY license. How we address one another says a great deal about our social relationships and which groups in society we belong to. This edited volume examines address choices in a range of everyday interactions taking place in Dutch, Finnish, Flemish, French, German, Italian and the two national varieties of Swedish, Finland Swedish and Sweden Swedish.